First records of Ochrotrichia Mosely, 1934 (Trichoptera: Hydroptilidae) in Northeastern Brazil: Five new species and two new geographical records - de Souza, Wagner Rafael M.; Santos, Allan Paulo Moreira; Takiya, Daniela M. (Zootaxa, 2014)
About 170 species have been assigned to the New World genus Ochrotrichia, only two of which were previously recorded from Brazil. Material collected in Bahia and Ceará states represent the first records of this genus from Northeastern Brazil and reveal five new species of Ochrotrichia. These are described and illustrated in this paper: O. caatinga sp. nov. (O. aldama group, from Ceará), O. priapo sp. nov. (O. aldama group, from Bahia); O. limeirai sp. nov. (O. aldama group, from Ceará), O. constricta sp. nov. (undetermined group, from Bahia), and O. igrapiuna sp. nov. (O. xena group, from Bahia). Ochrotrichia manuensis Flint & Bueno-Soria 1999 is firstly recorded from Brazil and O. patulosa (Wasmund & Holzenthal 2007) is firstly recorded from Northeastern Brazil.